1996
DOI: 10.1089/scd.1.1996.5.271
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Stem Cell Collection by Consecutive Courses of High-Dose Mobilizing Chemotherapy Using Cyclophosphamide, Etoposide, and G-CSF

Abstract: Tandem cycles of myeloablative chemotherapy can increase dose intensity and total dose of chemotherapy, but sufficient numbers of progenitor cells must be collected to ensure hematologic recovery after each treatment. This study was undertaken to determine if two courses of mobilizing chemotherapy given 4 weeks apart using cyclophosphamide 4000 mg/m2 and etoposide 400 mg/m2, combined with G-CSF 5-10 mg/kg on days 3-16 could each provide sufficient numbers of peripheral blood progenitor cells to support tandem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…[55][56][57] However, previous reports have shown that repeated chemotherapy courses, especially if given at short intervals, may severely hamper mobilization. 34 In particular, low mobilization has been observed after HD VP16 when delivered shortly after HD CY. 35 PBPC collections are only feasible if the mobilizing course is delivered after an adequate chemotherapy-free interval from a previous cytotoxic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[55][56][57] However, previous reports have shown that repeated chemotherapy courses, especially if given at short intervals, may severely hamper mobilization. 34 In particular, low mobilization has been observed after HD VP16 when delivered shortly after HD CY. 35 PBPC collections are only feasible if the mobilizing course is delivered after an adequate chemotherapy-free interval from a previous cytotoxic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] However, they may severely hamper mobilization, especially if given at short intervals. 34,35 This paper describes the evaluation of an innovative mobilizing procedure consisting of the administration of HD cyclophosphamide (CY) followed by HD ara-C, two drugs with a high mobilizing activity. Post-CY harvested PBPC were reinfused following HD ara-C to reduce hematological toxicity.…”
mentioning
confidence: 99%
“…33 However, using chemotherapy appears to impair the future mobilization of adequate numbers of CD34 ϩ cells. 12,34 We have provided evidence from a randomized study that G-CSF alone is adequate for progenitor cell mobilization. This was true, even in heavily pretreated patients with relapsed lymphoma.…”
Section: Hpc Mobilization For Autologous Transplantation 2063mentioning
confidence: 99%
“…[6][7][8] Similarly, low yields of CD34 + cells and hematopoietic progenitor/stem cells during peripheral blood mobilization regimens correlated with the type and timing of prior chemotherapy. [9][10][11] The causes for these deficiencies have not been ascertained.…”
mentioning
confidence: 99%